Impact of antiretroviral therapy on cutaneous adverse drug reactions in adult HIV patients: A study from a tertiary care hospital - Tulasi Jarang; Kavitha SB; Padma Akurathi; Bhumesh Kumar Katakam; Radhika AR; Suresh Babu Sayana (Asian Journal of Medical Sciences, 2024)
Background: Adverse drug reactions (ADRs) significantly impact public healthcare, especially among HIV patients. These reactions, which range from mild pruritus to severe conditions such as Steven-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), affect the quality of life and treatment outcomes. Aims and Objectives: The current study was designed to evaluate the various types of cutaneous ADRs (CADRs) in adult HIV patients undergoing antiretroviral therapy (ART). Materials and Methods: A retrospective record-based study was conducted at the Department of Dermatology, Venereology, and Leprosy, Government Medical College/Government General Hospital, Suryapet, Telangana, India. Data from November 2017 to October 2020 were analyzed, focusing on patients over 18 years on ART. Relevant demographic and medical data, including blood tests, liver and renal function, and CD4 counts, were collected. Results: Out of 3532 patients on ART, 568 (16.08%) developed CADRs. Females represented 54.2% of these cases. The age group most affected was between 29 and 48 years. The most common ART regimen was Tenofovir+Lamivudin+Dolutegravir, followed by zidovudine-based combinations. Nevirapine-based regimens had a higher association with CADRs, particularly severe reactions such as SJS and TEN. Conclusion: A significant proportion of HIV patients on ART experience CADRs, with certain drug combinations posing higher risks. This study highlights the need for careful monitoring and selection of ART regimens to minimize the risk of severe CADRs, thereby improving patient outcomes and quality of life in HIV treatment.